Synthesis and biological evaluation of N-cyanoalkyl-, N-aminoalkyl-, and N-guanidinoalkyl-substituted 4-aminoquinoline derivatives as potent, selective, brain permeable antitrypanosomal agents. Issue 21 (1st November 2016) - Sola, Irene; Artigas, Albert; Taylor, Martin C.; Pérez-Areales, F. Javier; Viayna, Elisabet; Clos, M. Victòria; Pérez, Belén; Wright, Colin W.; Kelly, John M.; Muñoz-Torrero, Diego
Graphical abstract: Abstract: Current drugs against human African trypanosomiasis (HAT) suffer from several serious drawbacks. The search for novel, effective, brain permeable, safe, and inexpensive antitrypanosomal compounds is therefore an urgent need. We have recently reported that the 4-aminoquinoline derivative huprine Y, developed in our group as an anticholinesterasic agent, exhibits a submicromolar potency against Trypanosoma brucei and that its homo- and hetero-dimerization can result in to up to three-fold increased potency and selectivity. As an alternative strategy towards more potent smaller molecule anti-HAT agents, we have explored the introduction of ω-cyanoalkyl, ω-aminoalkyl, or ω-guanidinoalkyl chains at the primary amino group of huprine or the simplified 4-aminoquinoline analogue tacrine. Here, we describe the evaluation of a small in-house library and a second generation of newly synthesized derivatives, which has led to the identification of 13 side chain modified 4-aminoquinoline derivatives with submicromolar potencies against T. brucei . Among these compounds, the guanidinononyltacrine analogue15e exhibits a 5-fold increased antitrypanosomal potency, 10-fold increased selectivity, and 100-fold decreased anticholinesterasic activity relative to the parent huprine Y. Its biological profile, lower molecular weight relative to dimeric compounds, reduced lipophilicity, and ease of synthesis, make it an interesting anti-HAT lead, amenable to further optimization to eliminate its remaining anticholinesterasic activity.